Evidence for the adaptive significance of an LTR retrotransposon sequence in a Drosophila heterochromatic gene - McCollum, Andrea M (BioMed Central, 2002)
BACKGROUND: The potential adaptive significance of transposable elements (TEs) to the host genomes in which they reside is a topic that has been hotly debated by molecular evolutionists for more than two decades. Recent genomic analyses have demonstrated that TE fragments are associated with functional genes in plants and animals. These findings suggest that TEs may contribute significantly to gene evolution. RESULTS: We have analyzed two transposable elements associated with genes in the sequenced Drosophila melanogaster y; cn bw sp strain. A fragment of the Antonia long terminal repeat (LTR) retrotransposon is present in the intron of Chitinase 3 (Cht3), a gene located within the constitutive heterochromatin of chromosome 2L. Within the euchromatin of chromosome 2R a full-length Burdock LTR retrotransposon is located immediately 3' to cathD, a gene encoding cathepsin D. We tested for the presence of these two TE/gene associations in strains representing 12 geographically diverse populations of D. melanogaster. While the cathD insertion variant was detected only in the sequenced y; cn bw sp strain, the insertion variant present in the heterochromatic Cht3 gene was found to be fixed throughout twelve D. melanogaster populations and in a D. mauritiana strain suggesting that it maybe of adaptive significance. To further test this hypothesis, we sequenced a 685bp region spanning the LTR fragment in the intron of Cht3 in strains representative of the two sibling species D. melanogaster and D. mauritiana (~2.7 million years divergent). The level of sequence divergence between the two species within this region was significantly lower than expected from the neutral substitution rate and lower than the divergence observed between a randomly selected intron of the Drosophila Alcohol dehydrogenase gene (Adh). CONCLUSIONS: Our results suggest that a 359 bp fragment of an Antonia retrotransposon (complete LTR is 659 bp) located within the intron of the Drosophila melanogaster Cht3 gene is of adaptive evolutionary significance. Our results are consistent with previous suggestions that the presence of TEs in constitutive heterochromatin may be of significance to the expression of heterochromatic genes.